1996
DOI: 10.2172/219359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of structural aging on seismic risk assessment of reinforced concrete structures in nuclear power plants

Abstract: The Structural Aging Program is addressing the potential for degradation of concrete structural components and systems in nuclear power plants over time due to aging and aggressive environmental stressors. Structures are passive under normal operating conditions but play a key role in mitigating design-basis events, particularly those arising from external challenges such as earthquakes, extreme winds, fires and floods. Structures are plant-specific and unique,.often are difficult to inspect, and are virtually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Sources of uncertainty must be considered in risk‐informed decision making based on PRA (Ellingwood & Song, ). A probabilistic model provides the framework for analyzing the sources of uncertainties.…”
Section: Assessment Of Food Insecurity In Gilroy Camentioning
confidence: 99%
“…Sources of uncertainty must be considered in risk‐informed decision making based on PRA (Ellingwood & Song, ). A probabilistic model provides the framework for analyzing the sources of uncertainties.…”
Section: Assessment Of Food Insecurity In Gilroy Camentioning
confidence: 99%
“…1, a PWR that was widely reviewed in various independent risk studies. The core damage was represented by a simple Boolean expression in this study to assess the risk significance of the structural degradation of the reinforced concrete beams and shear walls [Zion, 1981;Ellingwood and Song, 1996]. It was concluded that aging of structural components that appear as singleton cutsets in the plant logic has a minimal impact on core damage frequency due to seismic events (less than a factor of 2).…”
Section: Literature Review For Dac Developmentmentioning
confidence: 99%
“…This representation of the seismic fragility facilitates the development of an entire series of fragility curves for various levels of uncertainties. The seismic fragility analysis method based on this double lognormal model has been well studied and documented in the literature [e.g., Ellingwood, 1994, Ellingwood and Song, 1996, Kaplan, et al, 1989, Kennedy, et al, 1980, Kennedy and Ravindra, 1984.…”
Section: Overview Of Seismic Fragility Analysismentioning
confidence: 99%
“…Degradation of an SPC, often observed as loss of cross section or cracking, reduces the strength of the SPC and consequently causes the median fragility to decrease. However, the level of degradation may not affect the median fragility in a linear fashion, due to the dynamic nature of the seismic responses and also possibly the nonlinear behaviors of the SPC [Ellingwood and Song, 1996]. Since the degradation phenomena of SPCs have a significant amount of uncertainty and the knowledge for the development of the degradation models is not perfect, the uncertainty measures β R and β U increase as the SPCs age.…”
Section: Seismic Fragility Analysis Of Degraded Spcsmentioning
confidence: 99%